Principal Managerial Skills, Organizational Communication, Conflict Control, and Organizational Climate in Madrasah and Their Influence on Organizational Effectiveness - Salabi, Ahmad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research aims to analyze the relationship between school principals' managerial abilities, organizational communication, conflict control, and organizational climate with the organizational effectiveness of State Madrasah Aliyah in South Kalimantan Province. This research uses a quantitative approach with a survey method. Data was collected from 182 permanent teachers using proportional purposive sampling. The analysis was carried out using the SEM (Structural Equation Modeling) technique because this technique can be used to simultaneously answer regressive and dimensional problems. The LISREL (Linear Structure Relation) program version 8.30 was used as an analysis tool. Hypothesis test results show that: 1) The principal's managerial skills are directly related to organizational communication, conflict control, and organizational climate. 2) the principal's managerial skills indirectly relate to organizational effectiveness through conflict control and organizational climate as intervening variables. Organizational communication indirectly relates to organizational effectiveness through conflict control and organizational climate as intervening variables. Conflict control indirectly relates to organizational effectiveness through organizational climate as an intervening variable. This research provides implications regarding the importance of madrasah in taking concrete steps to increase the effectiveness of their organizations in achieving predetermined goals.